75-3(x+1)=22.33
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 29 – [16 + 3.(51 – 49)]
b) 5.22 + 98:72
c) 311 : 39 – 147 : 72
d) 295 – (31 – 22.5)2
718 : 716 +22.33
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
c) 5 8 : 5 6 + 2 2 . 3 3 - 2010 0 = 52 + 4 . 27 – 1 = 25 + 108 – 1 = 132
![](https://rs.olm.vn/images/avt/0.png?1311)
a)3\(^{11}\):3\(^9\)−147:7\(^2\)
=3\(^{11}\)\(^{-9}\)−147:49
=3\(^2\)−147:49
=9−3
=6
b)295−(31−22×5)w)295-(31-22×5)
=295−(31−2\(^2\).5)\(^2\)
=295−11\(^2\)
=295−121
=174
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a)\) \(5^{13}:5^{10}-25.2^2=5^3-25.4=125-100=25\)
\(b)\) \(20:2^2+5^9:5^8=20:4+5^1=5+5=10\)
\(c)\) \(100:5^2+7.3^2=100:25+7.9=4+36=40\)
\(d)\) \(84:4+3^9:3^7+5^0=84:4+3^2+1=21+9+1=31\)
\(e)\)
\(29-\left[16+3.\left(51-49\right)\right]=29-\left[16+3.2\right]=29-\left[16+6\right]=29-22=7\)
\(f)\) \(5.2^2+98:7^2=5.4+98:49=20+2=22\)
\(g)\) \(3^{11}:3^9-147:7^2=3^2-147:49=9-3=6\)
\(295-\left(31-2^2.5\right)^2=295-\left(31-4.5\right)^2=295-\left(31-20\right)^2=295-11^2=295-121=174\)
\(7^{18}:7^{16}+2^2.3^2=7^2+4.9=49+36=85\)
a: \(5^{13}:5^{10}-25\cdot2^2\)
\(=5^3-25\cdot4\)
=125-100
=25
b: \(20:2^2+5^9:5^8\)
\(=20:4+5\)
=5+5
=10
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{1}{2}x+\frac{3}{5}\left(x-2\right)=3\)
0,5 x + 0,6 ( x - 2 ) = 3
0,5 x + 0.6 x - 1,2 = 3
1,1 x = 4,2
x = \(\frac{42}{11}\)
Kết luận:
b) \(\frac{1}{3}x-0,5x=0,75\)
\(\frac{1}{3}x-\frac{1}{2}x=\frac{3}{4}\)
\(-\frac{1}{6}x=\frac{3}{4}\)
\(x=-\frac{9}{2}\)
Kết luận:
c) \(\frac{3}{-2}x-0,5x=75\%\)
-1,5x - 0,5x = 0,75
-2x = 0,75
x = -0,375
Kết luận:
d) \(-\frac{2}{5}x+\frac{1}{4}=75\%-\frac{3}{4}x\)
-0,4 x + 0,25 = 0,75 - 0,75 x
-0,4 x + 0,75 x = 0,75 - 0,25
0,35 x = 0,5
x = \(\frac{10}{7}\)
Kết luận:
\(a,\frac{1}{2}x+\frac{3}{5}\left(x-2\right)=3\)
\(\frac{1}{2}x+\frac{3}{5}x-\frac{6}{5}=3\)
\(\left(\frac{1}{2}+\frac{3}{5}\right)x-\frac{6}{5}=3\)
\(\frac{11}{10}x-\frac{6}{5}=3\)
\(\frac{11}{10}x=\frac{21}{5}\)
\(x=\frac{42}{11}\)
\(b,\frac{1}{3}x-\frac{1}{2}x=\frac{3}{4}\)
\(\left(\frac{1}{3}-\frac{1}{2}\right)x=\frac{3}{4}\)
\(\frac{-1}{6}x=\frac{3}{4}\)
\(x=\frac{-9}{2}\)
\(c,\frac{3}{-2}x-\frac{1}{2}x=75\%\)
\(\left(\frac{3}{-2}-\frac{1}{2}\right)x=\frac{3}{4}\)
\(-2x=\frac{3}{4}\)
\(x=\frac{-3}{8}\)
\(\frac{-2}{5}x+\frac{1}{4}=75\%-\frac{3}{4}x\)
\(\frac{-2}{5}x+\frac{3}{4}x=\frac{3}{4}-\frac{1}{4}\)
\(\left(\frac{-2}{5}+\frac{3}{4}\right)x=\frac{1}{2}\)
\(\frac{7}{20}x=\frac{1}{2}\)
\(x=\frac{10}{7}\)
`75-3.(x+1)=2^2 . 3^3`
`75-3.(x+1)= 4 . 27`
`75-3.(x+1)= 108`
`3.(x+1)=75 - 108`
`3.(x+1)= -33`
`x+1=(-33):3`
`x+1=-11`
`x=(-11)-1`
`x=(-12)`
Vậy `x=(-12)`
75-3x-3=4.27
72-3x=108
-3x=72-108
-3x=-36
x=12